Comparative Effects of Flipped Classroom Models on Critical Thinking and Collaboration Skills on Senior High School Biology - Randa M., Asty; Adnan; Dian Dwi Putri Ulan Sari Patongai (Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
Background: This study was conducted due to the need for innovative biology learning models that can enhance students’ critical thinking and collaboration skills, which remain insufficiently developed in conventional classroom learning. Methods: This research is a quasi-experimental with pretest-posttest control group design. Three XI classes at SMA Negeri 8 Makassar were used as samples. Experimental class 1 applied blended learning with problem-based flipped classroom type, experimental class 2 applied blended learning with traditional flipped classroom type, while one control class followed conventional learning. Critical thinking skills were measured using essay tests based on FRISCO indicators, and collaboration skills were measured through observation sheets. The data were analyzed with prerequisite tests (normality and homogeneity), which showed a significance value <0.05. Furthermore, ANCOVA test was conducted and continued with LSD test. Results: The results of the analysis showed that blended learning with a flipped classroom approach had a significant effect on improving students' critical thinking and collaboration skills. ANCOVA revealed a significant effect of learning model on critical thinking skills (F(2,84)=6.353, p=0.003) and collaboration skills (F(2,84)=7.197, p=0.001). In addition, the pretest covariate also significantly influenced critical thinking (F(1,84)=53.869, p<0.001) and collaboration skills (F(1,84)=372.999, p<0.001). LSD test results further showed significant differences among the experimental and control groups. Conclusions: The findings of this quasi-experimental study indicate that blended learning with a flipped classroom approach was more effective in enhancing students’ critical thinking and collaboration skills than conventional learning.